2020
DOI: 10.22541/au.159250166.69231945
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adsorption of Methyl Iodide on Reduced Silver-Functionalized Silica Aerogel: Kinetics and Modeling

Abstract: The low concentration methyl iodides (CH 3 I) adsorption process on reduced silver-functionalized silica aerogel (Ag 0 -Aerogel) was studied. The kinetic data were acquired using a continuous flow adsorption system. Because the corresponding physical process was observed, the shrinking core model (SCM) was modified and applied. An average CH 3 I pore diffusivity was calculated, the CH 3 I-Ag 0 -Aerogel reaction was identified as a 1.37 order reaction instead of first order reaction, and the n th order reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…48,49 Therefore, the higher iodine compositions for partially loaded Ag 0 -Aerogel observed by XPS indicate the existence of a strong concentration gradient in the pellet during the CH 3 I adsorption. Additionally, it can also be visualized that the concentrations of I on the surface are much higher than the experimental measured iodine uptakes (same as CH 3 I uptake, assuming CH 3 group diffuse out in C 2 H 6 form), which further supports the existence of the surface reaction proposed by Tang et al 23…”
Section: Surface Compositionsupporting
confidence: 82%
See 4 more Smart Citations
“…48,49 Therefore, the higher iodine compositions for partially loaded Ag 0 -Aerogel observed by XPS indicate the existence of a strong concentration gradient in the pellet during the CH 3 I adsorption. Additionally, it can also be visualized that the concentrations of I on the surface are much higher than the experimental measured iodine uptakes (same as CH 3 I uptake, assuming CH 3 group diffuse out in C 2 H 6 form), which further supports the existence of the surface reaction proposed by Tang et al 23…”
Section: Surface Compositionsupporting
confidence: 82%
“…For the chemisorption with gas phase product generated, Zhou and White 32 and Robb and Harriott 33 suggested that the formation of gases and the successive diffusion limitations may result in a fractional order reaction, which has been observed in the CH 3 I adsorption on Ag 0 -Aerogel by Tang et al 23 To explain this observation, a potential reaction pathway is proposed. Figure 6.…”
Section: Potential Reaction Pathway and Diffusion Limitationmentioning
confidence: 97%
See 3 more Smart Citations